2023
DOI: 10.1186/s13321-023-00722-y
|View full text |Cite
|
Sign up to set email alerts
|

OWSum: algorithmic odor prediction and insight into structure-odor relationships

Abstract: We derived and implemented a linear classification algorithm for the prediction of a molecule’s odor, called Olfactory Weighted Sum (OWSum). Our approach relies solely on structural patterns of the molecules as features for algorithmic treatment and uses conditional probabilities combined with tf-idf values. In addition to the prediction of molecular odor, OWSum provides insights into properties of the dataset and allows to understand how algorithmic classifications are reached by quantitatively assigning stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Lötsch et al [25] showed applications of olfactometric data with a set of unsupervised and supervised algorithms for pattern-based odor detection and recognition, odor prediction from physicochemical properties of volatile molecules, and knowledge discovery in publicly available big databases. Two different approaches to predict the structure-odor relationship with machine learning were conducted by Schicker et al [26]-who developed a classification algorithm that quantitatively assigns structural patterns to odors-and Bo et al [27], who used deep learning on the structural features for a binary two-class prediction of the odors. It was possible for Lee et al [28] to generate a principal odor map by constructing a message passing an artificial neural network (NN) to map chemical structures to odor percepts that enable odor quality prediction with human-level odor description performance and outperform chemoinformatic models.…”
Section: Modeling Aroma Partitioningmentioning
confidence: 99%
“…Lötsch et al [25] showed applications of olfactometric data with a set of unsupervised and supervised algorithms for pattern-based odor detection and recognition, odor prediction from physicochemical properties of volatile molecules, and knowledge discovery in publicly available big databases. Two different approaches to predict the structure-odor relationship with machine learning were conducted by Schicker et al [26]-who developed a classification algorithm that quantitatively assigns structural patterns to odors-and Bo et al [27], who used deep learning on the structural features for a binary two-class prediction of the odors. It was possible for Lee et al [28] to generate a principal odor map by constructing a message passing an artificial neural network (NN) to map chemical structures to odor percepts that enable odor quality prediction with human-level odor description performance and outperform chemoinformatic models.…”
Section: Modeling Aroma Partitioningmentioning
confidence: 99%
“…Such representations have therefore been used extensively with machine learning in previous works, like those to generate new molecular structures [13][14][15][16][17]. Additionally, other encoding schemes, such as molecular graphs [15,[18][19][20], have been widely combined with machine learning to predict molecular properties, like toxicity [21,22], medical activity in drug discovery [23][24][25][26], or even to predict the odor of molecules [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Such representations have therefore been used extensively with machine learning in previous works, like those to generate new molecular structures [13][14][15][16][17]. Additionally, other encoding schemes, such as molecular graphs [15,[18][19][20], have been widely combined with machine learning to predict molecular properties, like toxicity [21,22], medical activity in drug discovery [23][24][25][26], or even to predict the odor of molecules [27][28][29][30][31], among others actions.…”
Section: Introductionmentioning
confidence: 99%